Analisis Makna Mitos Dalam Cerita Rakyat Bhujuk Abdul Alam Prajjan - Mutmainnah Mutmainnah; Jatim Desiyanto; Wahidah Wahidah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Keguruan dan Ilmu Pendidikan PGRI Sampang, Indonesia, 2025)
Contained within it does not fade with the passage of time. This research is an effort to preserve the folk story of Bhujuk Abdul Alam Prajjan with the aim of analyzing the meaning of the myths contained within it, as well as the community's views on these myths in relation to social and cultural values. The research employs a descriptive qualitative method with Roland Barthes' semiotic theory to examine the denotative and connotative meanings in the story. Data is collected through observations, interviews with local communities, and documentation, then analyzed through stages of data collection, data reduction, data presentation, and verification. The research findings indicate that the myths in the folk story of Bhujuk Abdul Alam not only contain symbolic and spiritual values but also reflect the belief system of the Prajjan community. The myth of marriage with a fairy princess, the symbol of three rice strands, the arrival of invisible guests, and a buffalo nursing a child are understood as symbols of blessings, purity, and the grace possessed by Bhujuk Abdul Alam. The community view places Bhujuk Abdul Alam as a religious figure and a sacred ancestor worthy of honor, as well as a guardian of the cultural and spiritual identity of the Madurese people.